Getting Real How to Lead Authentically - Ruderman, Marian; Ruderman, Marian; Rogolsky, Sharon (Center for Creative Leadership, 2001)
Managers aren't always true to themselves. Sometimes, in a vain attempt to live up to organizational norms and expectations, their behaviors go against the grain of their own values. Without authenticity, leaders are less effective. By aligning your actions and your beliefs, you can reenergize yourself in both your work and your personal life.